THE STUDY OF PALMAR DERMATOGLYPHICS IN PSORIASIS. - DR. RAJESH DEHANKAR; DR. UJJWALA BHAKARE; DR. D. D. KSHEERSAGAR (International Journal of Pharma and Bio Sciences, 2013)
Dermatoglyphics is the scientific study of epidermal ridges on palms and soles. It is one of the recent and advancing of medical science. If there is any abnormality in the genetic make-up of parents it is inherited to the children and is reflected in dermatoglyphic pattern. This study is undertaken to find out correlation between dermatoglyphics and psoriasis. Psoriasis has been regarded as the “expression of disturbed environment and adaptation as between the patient and his environment.” Various dermatoglypic palmar patterns of psoriatic patients are studied. The present study is carried with an aim to study the dermatoglyphic trait in psoriasis in Maharashtra and compared them with the controls. The sexual and digital differences in dermatoglyphic patterns of psoriatics and controls are also seen. The present study is carried out in the department of anatomy, NKP SIMS, Nagpur. It consists of 600 subjects (300 psoriatics and 300 controls) whose palmar prints are collected from department of skin and venereal diseases. Prints are taken on maplitho paper by using printing ink and studied with magnifying lens. Various parameters of dermatoglyphics like finger tip patterns, palmar patterns, triradii, atd angle and a-b ridge count are analyzed by using Statistical calculations to find out the mean, standard deviation, coefficient of variation and chi-square test. After complete analysis it is concluded form the study that there is definitely a statistically significant difference in the dermatoglyphic patterns of psoriatics and controls. There is no regional difference but differences are found in the male and female subjects.